A Review of Character Strengths Interventions in Twenty-First-Century Schools: their Importance and How they can be Fostered - Lavy, Shiri (Applied Research in Quality of Life, 2020)
A main challenge of educational organizations is how to foster students’ capacity to fulfill their potential. The present paper, based on educational, psychological, and organizational research, asserts that a discussion of character strengths and their development is highly relevant to this challenge. It provides an integrative overview of the relevance of character strengths to twenty-first - century schools and discusses different mechanisms that can help foster them. Character strengths—widely valued positive traits, theorized to be the basis for optimal functioning and well-being—may derive from inner tendencies, but are expected to have broad potential for development, depending on individuals’ experiences and environments. Furthermore, character strengths are closely related to twenty-first-century competencies – cognitive, interpersonal and intrapersonal competencies, identified by the American National Research Council as required for thriving in contemporary life and work, and thus considered to be desirable educational outcomes. The paper first delineates the connections between twenty-first-century competencies and character strengths, demonstrating the importance of promoting them in education. Then, mechanisms for fostering development of character strengths in schools are discussed, based on a review of the literature, including mechanisms that affect students (e.g., curriculum, relationships), teachers (e.g., training, supervisors), and schools (e.g., evaluation processes, resource allocation), while considering the interplay between these different levels. The concluding part of the paper outlines an integrative model of an optimal school system, expected to foster character strengths’ use and development and discuss its applications for research and practice.